Performance evaluation of multi-even wireless sensor network using PMME priority protocol at mac layer with linear and nonlinear p-value sets - Nguyen, Chien Trinh (Journal of Military Science and Technology, 2024)
Among the MAC protocols that support multiple data priorities and save energy for multi-event wireless sensor networks, the PMME protocol is considered superior to its predecessors. However, these protocol simulation scenarios only consider the change in the number of nodes and have not yet implemented many p-value sets in the linear and nonlinear p-persistent CSMA/CA mechanism. In this paper, we analyze the influence of data priority p-value sets on multi-priority sensor network performance based on simulation of the operation of the MAC layer data-priority PMME protocol. The achieved results show that the PMME protocol uses a set of linear p-values to help the network maintain good network efficiency in terms of delay fairness while the nonlinear p-value helps the network ensure high priority will achieve a more optimal delay under simulation conditions with changes in the number of nodes and the set of priority p values for the four types of events.